Corrosion level estimation by means of the surface crack width. (1st August 2022) - Benenato, Armando; Ferracuti, Barbara; Imperatore, Stefania; Piero Lignola, Gian
Highlights: A wide and homogeneous database of experimental results relating the corrosion level and the surface cracking is collected. The reliability of the literature predictive models in estimating the crack width due to a given corrosion level is statistically interpreted. A novel formulation to evaluate the corrosion level from the average crack opening is proposed. Abstract: Since the concrete cover cracking is the earliest visible manifestation of corrosion, a relationship between crack opening and corrosion level can be a useful non-destructive tool to estimate the degradation level of an existing RC member. In the present paper, the predictive formulations available in the scientific literature estimating the crack width due to a given corrosion level are accurately described and their reliability is evaluated by a statistical analysis of the error in the predictions. At this aim, an extensive dataset on crack openings of artificially corroded RC specimen reinforced with a single bar, or more bars with large spacing, has been collected. Finally, a novel relationship for the assessment of the corrosion degradation from the surface cracking is presented and validated.